PENERAPAN PERMAINAN TRADISIONAL DAKON DALAM PEMBENTUKAN KARAKTER SISWA DI TK PGRI 02 AMBULU KAB. JEMBER - Jannah, Nurul Lailatul; Dahlan, Mukhtar Zaini; Prayogo, Basuki Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood education is a critical period that fulfills the development of individual character in the future.This study aims to examine the role of the traditional Dakon game in shaping the character of students at TK PGRI 02 Ambulu, Jember Regency. The issues raised are the reduced social interaction of children due to the dominance of digital games and the lack of understanding of character values in children. This study uses a qualitative descriptive approach with data collection techniques including in-depth observation, structured interviews, and careful documentation. The subjects of this study included 10 students from group B aged 5-6 years and active participation from teachers and parents in the observation process. The results of the study indicate that the Dakon game plays a very significant role in the development of children's character, especially in crucial aspects such as teamwork, individual responsibility, and improved social skills. Children involved in the Dakon game not only learn to appreciate and respect the decisions made by their friends, but also simultaneously acquire valuable cognitive skills through the dynamic interactions that occur during the game. This study concludes that the integration of traditional games such as Dakon into the early childhood education curriculum can be a very effective means of instilling positive character values from an early age. It is hoped that the preservation and sustainable utilization of traditional games in the context of education can increase children's awareness of the noble wealth of local culture.